EXPLORING CYBER SECURITY THREATS: A SYSTEMATIC LITERATURE REVIEW - Ahmad Farhan Mahesa; Arman Prasojo Sugiyarto; Rima Tamara Aldisa (Adisam Publisher, 2024)
This research aims to determine the challenges faced including political provocation, mis information (hoax), issues related to ethnicity, religion and race (SARA), hate speech, radical ideology, terrorism, hacking, data breaches, online fraud, and various other cybercrime. Proactive anticipation, prevention and mitigation strategies are very important to ensure cyber security. This research uses a systematic literature review method of various articles discussing cybercrime and cybersecurity in a systematic literature review of modern challenges. The research results show that continuous education and training is needed to increase digital literacy and cyber security awareness for effective protection. Synergy between stakeholders in increasing digital literacy and cyber security awarenessis very important.